AL-MUJMAL DAN AL-MUBAYYAN DALAM KAJIAN USHUL FIQH - Farid Naya (IAIN Ambon, 2013)
Quran and hadith is the source of Islamic Law, which the each used Arabic. So, to understand Islamic Law’s from Quran and hadith, must be understand about grammar language in the Arabic grammar and some of sentence in the Arabic text to find the meaning. One of the way to find the meaning from sentence’s of the Arabic text is Ushul Fiqh Approach. Kind of sentence in the Arabic text discussing here are al-Mujmal and Al-Mubayyan. By understanding those, we understand to Islamic law’s in Quran and Hadith as good and right until we can accomplish it by believe. Keywords: Al-Mujmal, Al-Mubayyan and Ushul Fiqh